2010
DOI: 10.1111/j.1462-5822.2010.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement driven innate immune response to malaria: fuelling severe malarial diseases

Abstract: SummarySevere malaria remains a major cause of global mortality. The innate immune response to infection is a key determinant of malaria severity and outcome. The complement system plays a key role in initiating and augmenting innate immune responses, including inflammation, endothelial activation, opsonization and coagulation, processes which have been implicated in malaria pathogenesis. In this review, we discuss the evidence supporting a role for excessive complement activation in the pathogenesis of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 77 publications
2
61
0
1
Order By: Relevance
“…The involvement of complement in Plasmodium infections has been widely reported in malaria literature (10, 112, 113) and extensively reviewed elsewhere (114). Different reports have demonstrated that during ma-laria, complement activation is increased (115,116).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…The involvement of complement in Plasmodium infections has been widely reported in malaria literature (10, 112, 113) and extensively reviewed elsewhere (114). Different reports have demonstrated that during ma-laria, complement activation is increased (115,116).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…However, complement activation is tightly regulated, and the loss of this control can contribute mechanistically to the pathogenesis of multiple conditions, including sepsis, asthma, transplant rejection, and neurodegenerative disorders (18,19,21,22,50). Although previous studies have reported activation of complement via several pathways during malaria infection (23), it has been difficult to determine whether excessive complement activation plays a causal role in the pathogenesis of severe disease in humans. In this study, we present several lines of evidence supporting a causal role for C5a-C5aR signaling in the pathogenesis of CM.…”
Section: Discussionmentioning
confidence: 87%
“…Increased complement activation has been consistently observed in human malaria infections (23). However, in human studies, it has been difficult to establish a causal role for complement activation in the pathogenesis of CM due to the challenges of performing mechanistic studies in human populations.…”
mentioning
confidence: 99%
“…4). These studies demonstrate that both the classical and the alternative complement pathways are activated in malaria, whereas the mannose-binding protein pathway is not significantly involved (4).…”
Section: The Canonical C5 Convertases Are Not Required For Ecm Develomentioning
confidence: 99%